UNA ENCUESTA DE INVESTIGACIÓN SOBRE LA DETERMINACIÓN DE LAS PERCEPCIONES DE PERFECCIONISMO MULTIDIMENSIONAL DE LOS ESTUDIANTES UNIVERSITARIOS EN EL NORTE DE CHIPRE - Ozuturk, Guliz; Dimililer, Celen (Revista Inclusiones, 2018)
The main aim of this study was to see whether the perfectionist personality trait in university students in Cyprus International University students predict their academic and daily life. This study investigated the multidimensional perfectionism in three phase: self-oriented, other-oriented and socially-oriented perfectionism. The research carried on in 2017-2018 academic year. A survey method is used to carry on the research. There are 230 university students and the age range of the students varies between 18-25. There are 120 female (52.2%) and 110 male (47.8%). Students are from special education (n=72), foreign language education (n=68) and basic education (n=90). There are 115 freshman and 115 senior students. In order to collect the data from participants 45 itemed Likert scale questionnaire is used. The outcomes of this research show that students’ perception of perfectionism between the number of siblings, other-oriented perfectionism with respect to gender and social-oriented perfectionism with respect to mothers’ education level, otheroriented perfectionism with respect to family income and students’ academic year at university have a significant difference